IMPLICATIONS OF LIFE IMPRESSION ON THE COMMUNITY SYSTEM IN INDONESIA - Androy Ade Rianda, (Proceeding International Conference on Social Sciences, 2026)
Many non-specialist legal experts are perplexed by the Indonesian Criminal Code since it does not include a maximum life sentence. As a substitute for the death penalty, courts in Indonesia often impose life sentences with the proviso that the defendant remains incarcerated indefinitely until he dies, as stated in Article 12 paragraph (1) of the country's criminal code. Both inflict mental and bodily pain on the incarcerated individual. We pose the research challenge in the following way: In the first place, how has the death penalty affected Indonesia's penal system? The second question is on the structure of life sentences under Indonesian law. One goal of this study is to analyze how Indonesia's penal system has changed since the death penalty was instituted. Furthermore, we need to know how life sentences are drafted under Indonesian criminal law. The research methodology used is known as normative legal research or library research, specifically referring to legal research that involves the examination and study of library resources. Final findings from the study. To begin, there are a number of inconsistencies between the rules laid forth in Indonesia's Criminal Code and Corrections Law and the realities within Indonesia's correctional facilities as a result of the life sentence policy. Second, the establishment of the life sentence as a criminal penalty in Indonesia. There are two kinds of jail terms outlined in Article 12 paragraph (1) of the Criminal Code, both of which entail life sentences, as stated in the Criminal Code (KUHP). According to Article 12 paragraph (4) of the Criminal Code, a life sentence indicates that the prisoner will be imprisoned until death, with a maximum term of twenty years.